2016
DOI: 10.1039/c5ta07036h
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient rutile TiO2photocatalysts with single Cu(ii) and Fe(iii) surface catalytic sites

Abstract: Highly active photocatalysts were obtained by impregnation of nanocrystalline rutile TiO 2 powders with small amounts of Cu(II) and Fe(III) ions, resulting in the enhancement of initial rates of photocatalytic degradation of 4-chlorophenol in water by the factor of 7 and 4, compared to pristine rutile, respectively. Detailed structural analysis by EPR and X-ray absorption spectroscopy (EXAFS) revealed that Cu(II) and Fe(III) are present as single species at the rutile surface. The mechanism of the photoactivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 69 publications
1
57
0
Order By: Relevance
“…These studies have shown a drastic enhancement of the bacterial inactivation kinetics of E. coli when Cu was added to binary-oxides in percentages from 0.01% (decoration) up to 1% (doping) [119,127,173]. A variety of TiO2-Cu preparations and the evaluation of their activity for diverse applications is an area of current interest [129][130][131]174]. The relevance of TiO2-Cu catalysts and photocatalysts addressing the issue of bacterial inactivation is reflected in the increasing number of studies focusing on the antibacterial effects of TiO2-Cu and TiO2/Cu in the form of 2D-coatings, suspensions, spheres, alloys, and decorated binary Next, we address the issue of the MRSA bacterial inactivation kinetics and relate the inactivation time to the applied light intensity.…”
Section: Interfacial Charge Transfer (Ifct) Suggested On Tio2-cu Filmmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have shown a drastic enhancement of the bacterial inactivation kinetics of E. coli when Cu was added to binary-oxides in percentages from 0.01% (decoration) up to 1% (doping) [119,127,173]. A variety of TiO2-Cu preparations and the evaluation of their activity for diverse applications is an area of current interest [129][130][131]174]. The relevance of TiO2-Cu catalysts and photocatalysts addressing the issue of bacterial inactivation is reflected in the increasing number of studies focusing on the antibacterial effects of TiO2-Cu and TiO2/Cu in the form of 2D-coatings, suspensions, spheres, alloys, and decorated binary Next, we address the issue of the MRSA bacterial inactivation kinetics and relate the inactivation time to the applied light intensity.…”
Section: Interfacial Charge Transfer (Ifct) Suggested On Tio2-cu Filmmentioning
confidence: 99%
“…These studies have shown a drastic enhancement of the bacterial inactivation kinetics of E. coli when Cu was added to binary-oxides in percentages from 0.01% (decoration) up to 1% (doping) [119,127,173]. A variety of TiO 2 -Cu preparations and the evaluation of their activity for diverse applications is an area of current interest [129][130][131]174].…”
Section: Interfacial Charge Transfer (Ifct) Suggested On Tio2-cu Filmmentioning
confidence: 99%
“…The relevance of the TiO 2 -Cu catalysts and photocatalysts addressing the issue of bacterial inactivation is reflected in the increasing number of studies focusing on the antibacterial effects of TiO 2 -Cu and TiO 2 /Cu in the form of 2D-coatings, suspensions, spheres, alloys, and doped binary oxides [169][170][171][172][173][174][175].…”
Section: Interfacial Charge Transfer (Ifct) Suggested On Tio 2 -Cu Fimentioning
confidence: 99%
“…To improve the photocatalytic activity of TiO 2 , modification of TiO 2 with transition metals such as inexpensive Fe(III) species has been widely studied. There are three main approaches to modifying TiO 2 with Fe(III): (1) doping of Fe(III) into the TiO 2 lattice to narrow the band gap or to introduce intraband impurity states for enhanced visible light activity [4][5][6]; (2) loading crystalline iron oxide (Fe 2 O 3 ) or iron oxyhydroxide (FeOOH) onto the TiO 2 surface and forming heterojunctions at the interface between Fe 2 O 3 and TiO 2 or between FeOOH and TiO 2 to enhance charge transfer between the two types of crystals [7][8][9][10]; (3) grafting highly dispersed Fe(III) ions or nanoclusters onto the TiO 2 surface to induce interfacial charge transfer (IFCT) from TiO 2 valence band (VB) to the Fe(III) states [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Different from doping, the grafting method uses a relatively low temperature and thus the Fe(III) locates on the surface rather than in the lattice of TiO 2 . The much lower amount of Fe used in grafting typically leads to the formation of isolated ions or clusters of Fe(III) species (iron oxide [14,15] or oxyhydroxide [11,13]). The IFCT from TiO 2 VB to Fe(III), because of the higher redox potential of Fe(III)/Fe(II) (0.77 V vs SHE) than the TiO 2 CB (~ 0V vs SHE), is the main reason for enhanced charge separation and visible light activity [11].…”
Section: Introductionmentioning
confidence: 99%